Answer:
D. domain: (-infinity, infinity); range: [1, infinity)
Step-by-step explanation:
The domain is the values that x can take
The domain is (-infinity, infinity)
The range is the values that y can take
absolute value is 0 or greater
cos x is from -1 to 1
The minimum value is when x=0
The smallest value is 1 and the largest is infinity
S=((294+3)*(294/3))/2=14553
We are asked to sum the two trinomials
![(-4f^3-5f+16)+(4f^2-f+9)](https://tex.z-dn.net/?f=%28-4f%5E3-5f%2B16%29%2B%284f%5E2-f%2B9%29)
. We can start by using the distributive property to remove the parenthesis, giving us
![-4f^3-5f+16+4f^2-f+9](https://tex.z-dn.net/?f=-4f%5E3-5f%2B16%2B4f%5E2-f%2B9)
. Next, when we combine like terms, we get
![\boxed{-4f^3+4f^2-6f+25}](https://tex.z-dn.net/?f=%5Cboxed%7B-4f%5E3%2B4f%5E2-6f%2B25%7D)
. Hope this helped!
Answer:
480 feet.
Step-by-step explanation:
We are told that the function
models Jason's height above ocean measured in feet as a function of time and t is the time in seconds from jumping off.
To find the height of cliff we need to substitute t=0 in our given function as at t=0 we will get Jason's height above ocean which is same as the height of the cliff.
Upon substituting t=0 in our function we will get,
![h(0)=-16(0)^2+16*0+480](https://tex.z-dn.net/?f=h%280%29%3D-16%280%29%5E2%2B16%2A0%2B480)
![h(0)=-0+0+480](https://tex.z-dn.net/?f=h%280%29%3D-0%2B0%2B480)
![h(0)=480](https://tex.z-dn.net/?f=h%280%29%3D480)
Since, the function gives Jason's height above ocean in feet, therefore, the cliff was 480 feet high.
Answer:
a. Total field goal points scored in the first two quarters, in simplest linear expression form is: 3x - 4.
b. The total points scored in the game, in simplest linear expression form is: 6x - 1.
a. The goal points scored in the first two quarters are expressed in linear forms as: 2x - 6 and x + 2.
The total field goal points in the first two quarters = 2x - 6 + x + 2
Add like terms
3x - 4
b. The total points scored in the game = 2x - 6 + x + 2 + 2x + x - 6 + 9
Add like terms and simplify the expression
2x - 6 + x + 2 + 2x + x - 6 + 9
6x - 1
Step-by-step explanation: